(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
Bioethical thinking regarding biotechnology should play an important role in our lives, views and legislation. The main debates have been and still are over the regulation, safety and moral status of certain applications of modern biotechnology, such as GMOs. There are fears about the technology being autonomous without public control due to its strategic nature. Awareness of technological impact on modern life is becoming more apparent as the application of biotechnology continues to develop. How then can we create a platform for handling biotechnology in a way that aligns with our views on the good life, ie. in a healthy, beneficial and environmentally sustainable way? This article therefore raises for discussion some important issues to consider regarding the ethical dimensions of technology and how it is used. Is it applied to the greater good? And do current regulations, or the lack of them, violate our responsibilities to others by not allowing them to choose whether they knowingly and voluntarily assume the risks of ingesting these GM substances?